Sol-gel derived silver doped nanocrystalline titania catalysed photodegradation of methylene blue from aqueous solution - Nur Amirah , Azhar (2012)
Titanium dioxide was widely used as photocatalyst for organic pollution degradation. Many researchers have reported that Ti0 2 is one of the most active catalyst in pesticides, phenols and the degradation of dyes. In this study, silver doped Ti02 nanoparticles (Ti0 2 -Ag) was succesfully prepared via sol-gel method and ultrasonic technique. For characterization of Ti0 2 -Ag, Thermal Gravimetric Analysis (TGA), X-Ray Diffaction (XRD) and Surface Area Analysis (BET) techniques were used. For the analysis of the photocatalytic reaction, Ti0 2 -Ag was undergo with the photodegradation of methylene blue (MB) dye in aqueous solutions and observed via UV-visible Spectroscopy. From the research, XRD showed the grain size of Ti02-Ag was smaller than commercialize titanium dioxide. For BET, the surface area of Ti0 2 -Ag was higher than commercialize than titanium dioxide. On the other hand, characterization by using TGA showed that Ti0 2 /P-25 and TiO 2 doped with silver were thermodinarnically stable. TiO 2 shows an intense absorption peak at 665 nm in UV and the intensity of this peak changes with concentration. The testing of the photo catalytic reaction of catalyst Ti0 2 was examined using the methylene blue with presence and absence of H 2 0 2. In this photocatalytic activity testing, the rate of the degradation MB were done and compared under various of conditions. This testing showed that the degradation of methylene blue was efficient by using Ti02-Ag compared to P-25. It was observed, in presence of oxidizing agent (11202), the rate of degradation methylene blue increases significantly.